2012
DOI: 10.1155/2012/605379
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Managers’ Leadership Styles in Finland

Abstract: Nurse managers who can observe their own behaviour and its effects on employees can adjust to a better leadership style. The intention of this study was to explore nurses' and supervisors' perceptions of nurse managers' leadership styles. Open-ended interviews were conducted with 11 nurses and 10 superiors. The data were analysed by content analysis. In the study, six leadership styles were identified: visionary, coaching, affiliate, democratic, commanding, and isolating. Job satisfaction and commitment as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 37 publications
0
34
0
3
Order By: Relevance
“…A key question is how appropriate skills nurse managers have in utilising nursing research findings and translating them into practice [18]. According to earlier research findings, nurse managers wish for more time to articulate their vision [33], while nurses emphasize the importance of making the vision understandable by providing information about current issues [28]. These perceptions probably show a contradiction between the vision of the organization and the skills and resources available for its implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A key question is how appropriate skills nurse managers have in utilising nursing research findings and translating them into practice [18]. According to earlier research findings, nurse managers wish for more time to articulate their vision [33], while nurses emphasize the importance of making the vision understandable by providing information about current issues [28]. These perceptions probably show a contradiction between the vision of the organization and the skills and resources available for its implementation.…”
Section: Resultsmentioning
confidence: 99%
“…In the second part the purpose of the study was to discover nurse managers' perceptions of their leadership styles and the factors influencing it [27]. The third part of the study consisted of exploring how nurses and superiors perceive nurse managers' leadership styles and the factors affected by leadership styles [28]. The aim of the present paper is to explore nurse managers' perceptions related to their leadership styles, knowledge, and their skills in these areas in health centre wards in Finland.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Una línea de investigación en este sentido podría ser comparar la autopercepción de los responsables con la visión de los profesionales, para encontrar los puntos de consenso y divergencias y optimizar así los estilos de dirección 31 , ante la evidencia de que, en el contexto asistencial hospitalario, una dirección y coordinación óptima maximizarían la satisfacción de los pacientes 32 . …”
Section: Discussionunclassified
“…To realize such leadership, managers need to apply a coaching approach based on trusting relationships with the professional workers. This means that the managers must respect the professional workers' skills and established work routines, giving them the freedom to act independently, and avoid micromanaging (Andreasson et al, 2015;Vesterinen et al, 2012). It has been demonstrated that some health care managers delegate developmental tasks to professional workers without following up on the results and without checking whether they possess the knowledge needed to undertake the delegated tasks (Andreasson et al, 2015).…”
Section: Power To Changementioning
confidence: 99%